The complementarity between the internal audit and the audit committees, and its role in supporting and enshrining the corporate governance - BISSAR , Abdelhakim (Journal of Research in Finance and Accounting, 2023)
The study aims at showing the role of the complementary relation between the internal audit and the audit committees in supporting and enshrining the principles of the corporate governance. Findings show that the internal audit is one of the main mechanisms that allow the promotion of the corporate governance and the achievement of its goals through the complementarity and interaction with the various administrative bodies that include the administration council, the higher administration, the audit committee, and the external auditor because it helps them exercise their roles. In this line, this complementary relation manifests more between the internal audit and the audit committees because the first supports the second in meeting their responsibilities in the corporate governance and in the quality of the financial reports issued by the administration. On the other hand, the audit committee provides the suitable environment for the internal audit to perform its governance tasks. Thus, the effective audit committee reinforces the internal audit. Besides, this complementary relation increases the ability of the internal audit and the audit committee to support the corporate governance.